Designing engobe coatings for ceramic bricks - Khomenko, Olena; Tsyhanenko, Liudmyla; Tsyhanenko, Hennadii; Borodai, Artem; Borodai, Dmytro; Borodai, Serhii (Eastern-European Journal of Enterprise Technologies, 2023)
This paper reports research into the development of compositions of engobe coatings for ceramic bricks and investigating the influence of technological production factors on their physical and mechanical properties. The results of this work make it possible to solve the task of expanding the range and improving the operational properties of building ceramics. The data obtained have made it possible to establish physicochemical processes occurring during the formation of the phase composition and structure of engobe coatings. This has revealed the possibilities for designing engobe for various types of ceramic bricks, which differ in technological parameters of production and operational properties. The charge compositions were designed in a three-component system "refractory clay – quartz sand – cullet", taking into account the possibility of their practical implementation in large-tonnage production. It has been established that the most important condition for obtaining high-quality products is the correlation of shrinkage and temperature coefficients of linear expansion of the ceramic shard and engobe coating. To prevent various defects, these indicators should vary by no more than 10 %. The crystal-phase composition of engobe is represented by b-quartz and a small amount of devitrite, which are evenly distributed in a vitreous dense layer of coating on the surface of the ceramic shard. Distinctive features of the results relate to the fact that a solution to the problem of designing engobe coatings for ceramic bricks has been proposed and the physicochemical bases of production have been highlighted. This paper also suggests ways to achieve coordination of finely dispersed coatings with coarse-grained ceramic masses by shrinkage and thermal processes. The results reported here could be applied in typical production of face, clinker, and in some cases – ordinary brick or ceramic stone with firing temperatures of 950–1150 °C